The effect of groundstroke forehand exercise on enhancing cardiorespiratory endurance (VO2 MAX) in 12- to 14-year-old tennis athletes - Syahriadi; FX. Sugiyanto; Ria Lumintuarso; Ardiah Juita; Trisnar Adi Prabowo (SPORT TK-EuroAmerican Journal of Sport Sciences, 2024)
This study aimed at investigating groundstroke forehand exercise’s effect on improving tennis athletes’ cardiorespiratory endurance (VO2Max) for six weeks. This quasi-experiment research was carried out using a randomized pre-test and post-test group design. The population of this research was 35 tennis athletes aged 12-14 years old. Using purposive sampling, the sample in this study was 20 people, and the sample was taken based on 12-14-year-old tennis athletes who were technically good. The exercise was divided into seven models, namely forehand turn core, forehand turn cone back cone, forehand forward-direction, forehand hurdle jump, forehand sideways, forehand turn cone center service to baseline, forehand one-way service center to baseline. Those exercise models have earned a decent category for use in training. An instrument used for measuring cardiorespiratory endurance (VO2Max) was multistage (bleep test). The data analysis for this study comprised descriptive analysis, prerequisite tests such as normality and homogeneity checks, and the application of the sample paired t-test to test hypotheses. Based on the results, groundstroke forehand training can improve the cardiorespiratory (VO2Max) of tennis athletes aged 12-14 years old for six weeks (p<0.05) Thus, this research can be a basis for coaches and athletes to improve cardiorespiratory or VO2Max. Further research is expected that groundstroke forehand exercise can be combined with other techniques or used to analyze the ability of tennis athletes.